Antimicrobial prescribing practices for enteric bacterial infections in an integrated health care system, Wisconsin, 2004–2017 - Scott C. Olson; Louise K. Francois Watkins; Elaine Scallan Walter; Cindy R. Friedman; Huong Q. Nguyen (Journal of Infection and Public Health, 2025)
Background: Few studies have evaluated antibiotic prescribing practices for bacterial enteric infections. Unnecessary antibiotics can result in adverse events and contribute to the emergence of antimicrobial resistance. We assessed treatment practices among patients with laboratory-confirmed enteric infections in a regional healthcare system in Wisconsin, USA. Methods: We used electronic health records to identify patients with laboratory-confirmed nontyphoidal Salmonella, Shigella, Shiga toxin-producing Escherichia coli (STEC), and Campylobacter infections during 2004–2017. Relevant clinical data, including diagnosis codes for chronic conditions and receipt of immunosuppressive medications and antibiotic prescriptions, were extracted. We defined appropriate treatment based on pathogen, patient characteristics, and practice guidelines for the study period. Results: We identified 2064 patients infected with Campylobacter (1251; 61 %), Salmonella (564; 27 %), STEC (199; 10 %), or Shigella (50; 2 %). Overall, 425 (20 %) patients were immunocompromised, ranging from 17 % with Salmonella to 46 % with STEC. There were 220 (11 %) hospitalizations. Antibiotics were prescribed most frequently for Campylobacter (53 %), followed by Shigella (46 %) and Salmonella (44 %) infections. Among those prescribed antibiotics, prescriptions were appropriate for 71 % of Campylobacter, 100 % of Shigella, and 81 % of Salmonella infections. Antibiotics were prescribed for 24 % of STEC infections, despite recommendations against use. Guideline adherence generally decreased with age, except for Shigella infections, where adherence was highest for adults ≥ 50 years. Conclusions: Antibiotic prescribing for laboratory-confirmed enteric infections was usually appropriate but did not follow practice guidelines in a substantial minority of cases, presenting opportunity for improvement. Antibiotic stewardship initiatives should address acute bacterial gastrointestinal infections in addition to other common infections.